Leadership And Organization on Nurses' Performance - Arniti; Fadhilah , Harif; Widiastuti , Eni; Hadi , Muhamad; Nawangwulan , Rahayu (PT. Anagata Sembagi Education, 2025)
Nurse performance is a series of activities in providing nursing care which is a process or nursing practice activities provided by nurses to patients using the nursing process. Poor performance can be caused by ineffective leadership. As a form of supervision, a leader can use a performance appraisal system to support optimal organization. Organizing is the process of managing and directing all assets, including the workforce, so that they can collaborate and synergize effectively and ensure that each element clearly understands their respective roles, obligations, and areas of responsibility. The purpose of this study was to identify the relationship between the leadership of the ward head and organization with the performance of nurses in the inpatient ward of the Jakarta Islamic Hospital Sukapura. The study design was cross-sectional. The number of samples in this study was 75 respondents with a selection technique while using the total sampling technique. The analysis used was univariate, bivariate, and multivariate analysis. The results of the study showed that there was a relationship between the leadership of the head of the room and the performance of nurses (p = 0.001), there was a relationship between organization and nurse performance (p = 0.000), there was no relationship between length of service (p = 1.000), there was no relationship between education (p = 0.783), there was no relationship between gender (p = 0.757), and there was no relationship between age and nurse performance (p = 0.658). Organization is the most dominant factor that influences nurse performance. Hospital management should evaluate the inpatient organizational structure with a more effective command flow and span of control of the head of the room that allows each nurse to receive supervision, thereby improving nurse performance in providing nursing care services